Bilateral mumps in an adult female mimicking mandibular lesions on panoramic radiography: a case report - Fauziyah, Erlina; Epsilawati, Lusi; Lubis, Ratih Trikusumadewi (Ikatan Radiologi Kedokteran Gigi Indonesia, 2026)
Objectives: The purpose of this case study is to report a case of quite painful facial swelling observed on a panoramic radiograph and diagnosed as Bilateral Mumps. Case Report: A 34-year-old woman came to the Radiology Department with complaints of throbbing pain accompanied by swelling in the right and left mandible. The swelling has been present for 5 days, and the pain worsens when eating. In addition, the patient complains of having a fever and being unable to sleep. Physical examination revealed a body temperature of 38.6°C; the patient appeared lethargic and weak. Extraoral examination shows the lower part of the face is swollen, symmetrical between the left and right sides, with increased surface temperature of the lesion, and upon palpation, it feels soft and painful when touched. During the intraoral examination, no swelling was observed. The results of the panoramic radiograph examination show a diffuse radiolucent image spread from the angle to the ramus of the left and right mandible. There are no changes in the structure of the cortical bone of the mandible. From the panoramic examination, a suspect radiodiagnosis of bilateral mumps on the right and left mandible was found. Conclusion: Mumps is an infection of the salivary glands caused by a virus. On panoramic radiography, the image is more indicative of the formation of osteolytic lesions in the form of radiolucent foci with varying diameters and ill-defined borders. Pockets spread in the inflamed area, and in this case, panoramic radiography can recognize the condition.